Innovation in local economies Germany in comparative context - Crouch, Colin, 1944-; Voelzkow, Helmut (Oxford : Oxford University Press, 2009)
The study of varieties of capitalism is moving from analysis of static national types to embrace local and sectoral diversity and systems in the process of major change. This volume addresses the issue by examining four localised sectors comparing Germany with other European countries, including the UK, Sweden, and Hungary.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Industries -- Germany -- Case studies; Technological innovations -- Economic aspects -- Germany -- Case studies; Germany -- Economic conditions -- 1990- -- Regional disparities